Social Quarantine and Its Four Modes: Conceptional Exploration and the Theoretical Construction of the Policies Against COVID-19 - Lin, Ka; Mumtaz, Ayesha; Rahaman, Mohammad Anisur; Mok, Ka Ho (Frontiers in Public Health, 2021)
Building on the studies of health quarantine from a social perspective, this article explores the complex contexts of social quarantine as a mode of public health, a mode of community action and a behavioural and psychological mode of social distancing. To establish a conceptual investigation of the “social quarantine” issue, this study investigates four approaches to quarantine: public health, social administration, behavioural norms, and psychological effects. The study identifies the features of these modes and discusses their relationships. In addition, this study constructs a preventive framework for quarantine that embraces social and health policies to enrich the understanding of policy measures for social distancing and lockdown measures. On this basis, the study evaluates the strategies of policy development in response to the COVID-19 pandemic. The study concludes that these modes can reconstruct social relations and provide some basis for theoretical analysis about the features of social quarantine, which is vital for policymakers when considering national and global prevention strategies for public health.